2015
DOI: 10.11591/eecsi.v2.773
|View full text |Cite
|
Sign up to set email alerts
|

Application of NFC Technology for Cashless Payment System in Canteen

Abstract: In a campus community, mostly is younger people and stay in University hostel without cooking facilities then have to get from canteen for foods and beverages. In office hour with limited break time either breakfast or lunch everyone is rushing to get food and crowded situation are happen. One of the issues is payment system use manually (cash) and queue at the cashier to pay foods, sometime need to wait a few minute until to get the turn. Cashless payment such as token or credit system is implementing in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Kadir et al [5] concluded in their study that NFC technology in campus canteen pose an effective transaction and security for the students. As NFC payment is cashless, this also solves the issue of long queues in canteens due to the slow traditional process of payment.…”
Section: Literaturementioning
confidence: 99%
“…Kadir et al [5] concluded in their study that NFC technology in campus canteen pose an effective transaction and security for the students. As NFC payment is cashless, this also solves the issue of long queues in canteens due to the slow traditional process of payment.…”
Section: Literaturementioning
confidence: 99%
“…Cashless payments are also seen as more hygienic for food vendors [3]. Cashless modes for small payments, such as Near Field Communication (NFC) technology, are found to be able to reduce queueing and the need to carry cash for high-volume and low-value transactions [4,5]. In a recent study, Kilay, Simamora and Putra [6] show that the supply chain performance of micro, small, and medium enterprises in Indonesia is directly correlated with the use of e-payment services.…”
Section: Introductionmentioning
confidence: 99%